Dashboard Pemantauan Real-Time Untuk Mengurangi Keterlambatan Penanganan Gizi Buruk - Farhan Aditya Pranowo; Riska Maulida Hartanti (Community : Jurnal Pengabdian Pada Masyarakat, 2026)
Community-level management of acute malnutrition continues to face challenges due to slow and fragmented manual reporting systems, resulting in delayed interventions after children’s conditions deteriorate. This community service-based study aimed to develop and evaluate the effectiveness of a real-time monitoring dashboard in accelerating reporting and response to severe malnutrition cases. A quasi-experimental pre–post design with a cluster control group was employed using a mixed-methods approach. The study involved 200 children under five years old, community health volunteers, and health workers. Data were collected from anthropometric records, dashboard log data, perception surveys, interviews, and focus group discussions. The results indicate that implementing the real-time dashboard significantly reduced reporting time from an average of 14 hours to 3 minutes, accelerated health worker response time to less than 1 hour, and decreased case management delays from 62% to 18% (p < 0.001). In addition, the completeness of recorded anthropometric data improved consistently. This study demonstrates that integrating a real-time dashboard into community-based service workflows substantially enhances the responsiveness, accuracy, and flexibility of nutrition reporting systems, supporting the broader adoption of digital real-time solutions to strengthen severe malnutrition management at the grassroots level.